2018
DOI: 10.1371/journal.pone.0200347
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein electrophoresis in healthy and injured southern white rhinoceros (Ceratotherium simum simum)

Abstract: Investigation of globulin fractions by serum protein electrophoresis (SPE) is the first step towards evaluation of the proteome in the southern white rhinoceros (Ceratotherium simum simum). Furthermore, identification of changes in globulins in animals with poaching and other injuries can guide discovery of potentially useful biomarkers of inflammation. The aim of this study was to develop reference intervals for agarose gel SPE in healthy white rhinoceros and to compare these serum protein electrophoresis res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…Among these is the general rule that the α‐2/β‐1 demarcation typically lies at approximately the halfway point of the electrophoretogram . Calculation of relative migration distance has been advocated to help determine peaks and demarcation points between fractions . The relative migration distance reportedly allows a degree of standardization between different electrophoretic runs and can be calculated using the equationRelativemigrationdistance=DistancefromtheapplicationpointtoaspecificlocationDistancefromtheapplicationpointtoalbumin×100…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these is the general rule that the α‐2/β‐1 demarcation typically lies at approximately the halfway point of the electrophoretogram . Calculation of relative migration distance has been advocated to help determine peaks and demarcation points between fractions . The relative migration distance reportedly allows a degree of standardization between different electrophoretic runs and can be calculated using the equationRelativemigrationdistance=DistancefromtheapplicationpointtoaspecificlocationDistancefromtheapplicationpointtoalbumin×100…”
Section: Methodsmentioning
confidence: 99%
“…In most settings, chemically determined albumin is expected to be higher than densitometric albumin, due to binding of the bromocresol green dye to α‐ and β‐globulins . Additionally, some albumin has been shown to electrophoretically migrate in the globulin fraction of several species . M‐proteins can cause a significant falsely increased or decreased colorimetric albumin concentration, and in cases where the M‐protein is not soluble under the conditions of the total protein measurement, M‐proteins can cause falsely decreased total protein measurements (Figure ) …”
Section: Methodsmentioning
confidence: 99%
“…Polyacrylamide gel electrophoresis was taken as a biomarker for many immunological and toxicological studies (Muhammad et al, 2018). Profiling of serum proteins facilitates identification of many issues related to diseases and inflammation in mammals and fish (Akbary & Jahanbakhshi, 2018;Hooijberg et al, 2018;Yang, Cho, Wang, Park, & Yang, 2016). Serum protein usually separates into albumin and globulins fractions: α1, α2, β1, β2 and γ according to their sizes and electrical charges (Christiansen et al, 2015;Jenkins, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, selecting captive WR instead of free-ranging BR as the negative control precisely aimed at limiting the captivity bias since captivity may be pro-inflammatory by itself [37,53]. Serum protein electrophoretic results of the captive WR included in this study showed some variations in comparison to healthy free-ranging WR [31], further underlining the interest of selecting captive WR as a control group in order to limit the captivity bias. Obesity is described for being pro-oxidative and pro-inflammatory [54], but no study to date investigates the consequences of overweight in rhinoceroses.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation status was evaluated by measuring total serum protein (TP, biuret method) and agarose gel electrophoretic albumin and globulin fractions (albumin and globulins including α 1 -, α 2 -, β- and γ-globulin fractions, agarose gel method (Hyrys2, Hydragel; Sebia, Evry, France). Globulin fractions were determined according to recent published data from Hooijberg and colleagues [31]. α 1 -globulins refers to α 1 -a and α 1 -b fractions, and β-globulins refers to β1 and β2 fractions.…”
Section: Methodsmentioning
confidence: 99%